Market power and the feedback effects from hedging derivatives - Rosário, J.; Amaro de Matos, J. (International Journal of Theoretical and Applied Finance, 2002)
In this paper we model how the transaction of derivatives affects the price process of the underlying asset, considering the existence of a few agents with market power and a population of liquidity traders. This setting generates an equilibrium bid-ask spread for the underlying asset. The resulting feedback effect of hedging strategies is shown to depend on what type of agent more actively hedges. We also characterize how the feedback effect is lessened as the number of market-makers increases.